2014
DOI: 10.1371/journal.pone.0087665
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Screening Identified That miR-134 Acts as a Metastasis Suppressor by Targeting Integrin β1 in Hepatocellular Carcinoma

Abstract: MicroRNAs (miRNAs) are small, single-stranded, non-coding RNAs that play pivotal roles in human cancer development and progression, such as tumor metastasis. Here, we identified the miRNAs that regulate hepatocellular carcinoma (HCC) cell migration by a high-throughput screening method using the classical wound-healing assay with time-lapse video microscopy and validation with a transwell migration assay. Eleven miRNAs (miR-134, -146b-3p, -188-3p, -525-3p, -661, -767-5p, -891a, -891b, -1244, -1247 and miR-1471… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
67
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 39 publications
0
67
0
Order By: Relevance
“…Overexpression of miR-134 in HCC cells arrested cell growth and decreased cell migration and invasion by downregulating the oncoprotein KRAS. Zha et al (2014) also revealed that miR-134 suppressed the invasion and metastasis of HCC cells in vitro and in vivo, and integrin beta 1 was a direct and functional target gene of miR-134 (Zha, et al, 2014). In non-small cell lung cancer, miR-134 inhibits the invasive potential and epithelial-to-mesenchymal transition phenotype of tumor cells, and directly targets FOXM1 (Li et al, 2012), a potential metastasis promoter.…”
Section: Discussionmentioning
confidence: 95%
“…Overexpression of miR-134 in HCC cells arrested cell growth and decreased cell migration and invasion by downregulating the oncoprotein KRAS. Zha et al (2014) also revealed that miR-134 suppressed the invasion and metastasis of HCC cells in vitro and in vivo, and integrin beta 1 was a direct and functional target gene of miR-134 (Zha, et al, 2014). In non-small cell lung cancer, miR-134 inhibits the invasive potential and epithelial-to-mesenchymal transition phenotype of tumor cells, and directly targets FOXM1 (Li et al, 2012), a potential metastasis promoter.…”
Section: Discussionmentioning
confidence: 95%
“…In hepatocellular carcinoma, miR-134 suppressed cell metastasis by regulating the expression of integrin β1 (19). In glioma, the downregulation of miR-134 expression is typical, and cell growth, migration and invasion was inhibited by the upregulation of miR-134; miR-134 overexpression also enhanced cell apoptosis in human glioma cells (20).…”
Section: Discussionmentioning
confidence: 98%
“…miR-134 has been previously demonstrated to function as a tumor suppressor in several types of tumors (18)(19)(20). In hepatocellular carcinoma, miR-134 suppressed cell metastasis by regulating the expression of integrin β1 (19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More and more upstream regulator genes related to tumor metastasis, such as pre-transfer microRNA and anti-metastatic microRNA, are found to have an important role in the invasion and metastasis of HCC. Genome-wide screening has identified that miR-134 acts as a metastasis suppressor by targeting integrin beta 1 in hepatocellular carcinoma [26]. microRNA-21, which can change the focal adhesion kinase (FAK) expression and phosphorylation of MMP2 and MMP9 matrix metalloproteinase, together with the downstream regulator of PTEN, participate in the metastasis and invasion of tumor cells.…”
Section: Micrornas and Metastasis Of Hccmentioning
confidence: 99%